Physics education students' perception on the use of motion detector in linear motion practicum - Hariwangsa Panuluh, Albertus; Dian Atmajati, Elisabeth; Dwi Kristanto, Yosep (Journal of physics. Conference series, 2020)
The use of technology in teaching and learning is very common today. In physics learning, practicum has an important role, namely deepening the understanding of concepts and applying concepts. However, it is interesting to know the importance of using technology in practicum. This study aims to know to know the student's Physics education students' perception on the use of motion detector in linear motion practicum The present study was descriptive research using a qualitative approach. This research was carried out in mechanics experiment class with 16 students as research subjects. This study used students' reflection and interview in collecting perception's of the students. The research found that practicum with motion detector has significant role in results obtained. On the other hand, practicum with motion detector has unsignificant role in the student's carefullness.